2011
DOI: 10.1038/ismej.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of anthropogenic activity on the ecology of class 1 integrons and integron-associated genes in the environment

Abstract: The impact of human activity on the selection for antibiotic resistance in the environment is largely unknown, although considerable amounts of antibiotics are introduced through domestic wastewater and farm animal waste. Selection for resistance may occur by exposure to antibiotic residues or by co-selection for mobile genetic elements (MGEs) which carry genes of varying activity. Class 1 integrons are genetic elements that carry antibiotic and quaternary ammonium compound (QAC) resistance genes that confer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
218
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(237 citation statements)
references
References 42 publications
16
218
1
2
Order By: Relevance
“…We believe this is the first study to determine the effects from the direct application of veterinary antibiotics in the absence of manure with the resolution achievable by16S rRNA gene sequence analysis. We have shown that a decade of annual exposure to a mixture of antibiotics at 10 mg kg -1 led to a statistically significant H. Gaze, personal communication) (Gaze et al, 2011). The 0.064% observed in treatment plots was higher than that previously observed in soil that had undergone application of antibiotic amended pig slurry (0.01%) (Byrne-Bailey et al, 2011), and soil 12 months after sewage cake application (0.02%) (Gaze et al, 2011) but lower than one month after application (0.36%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We believe this is the first study to determine the effects from the direct application of veterinary antibiotics in the absence of manure with the resolution achievable by16S rRNA gene sequence analysis. We have shown that a decade of annual exposure to a mixture of antibiotics at 10 mg kg -1 led to a statistically significant H. Gaze, personal communication) (Gaze et al, 2011). The 0.064% observed in treatment plots was higher than that previously observed in soil that had undergone application of antibiotic amended pig slurry (0.01%) (Byrne-Bailey et al, 2011), and soil 12 months after sewage cake application (0.02%) (Gaze et al, 2011) but lower than one month after application (0.36%).…”
Section: Discussionmentioning
confidence: 87%
“…We have shown that a decade of annual exposure to a mixture of antibiotics at 10 mg kg -1 led to a statistically significant H. Gaze, personal communication) (Gaze et al, 2011). The 0.064% observed in treatment plots was higher than that previously observed in soil that had undergone application of antibiotic amended pig slurry (0.01%) (Byrne-Bailey et al, 2011), and soil 12 months after sewage cake application (0.02%) (Gaze et al, 2011) but lower than one month after application (0.36%). Integron prevalence in aquatic sediments has been shown to correlate with specific land uses (Amos et al, 2014), suggesting terrestrial inputs into river catchments and ultimately to receiving coastal waters where human exposure may occur (Leonard et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…In this study, it was found that intI1 gene had significantly positive correlation with sulI, sulII, tetA, tetC, tetG, and tetBP genes, indicating that intI1 gene may play certain role in the dissemination of ARGs. Previous study have demonstrated that integrons can be used by Gram-positive and Gram-negative bacteria to stockpile and express different exogenous resistance genes and are considered to play a central role in the worldwide problem of antibiotic resistance [39][40][41]. Partridge et al found that sulI gene was carried within the 3 conserved region of class 1 integron, and such an association may facilitate and enhance its persistence [42].…”
Section: Discussionmentioning
confidence: 99%
“…HGT could potentially enhance the accumulation and persistence of ARGs in manure/sludge-amended soil via MGEs (Gaze et al, 2011;Smalla et al, 2000). It has been demonstrated that MGEs, especially integrons can be used by bacteria to stockpile and express different exogenous resistance genes and are considered to play a central role in the worldwide problem of antibiotic resistance (Gaze et al, 2011;Gillings et al, 2008;Partridge et al, 2009). Our results indicated that MGEs had significantly positive correlation with resistance genes to beta-lactams, MLSB, sulfonamide and vancomycin, while no significant correlation with resistance genes to tetracyclines.…”
Section: Horizontal Transfer Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…Land application of sewage sludge may result in the spread of ARGs in soil and to underground water (Threedeach et al, 2012). More importantly, bacteria have been shown to readily share genetic information by HGT via mobile genetic elements (MGEs) including plasmids, transposons, and integrons (Zhu et al, 2013;Pruden et al, 2006), allowing the transfer of resistance genes from sewage sludge microorganisms to indigenous environmental bacteria (Gaze et al, 2011). Sewage sludge has been shown to be a hotspot for bacteria carrying ARGs and MGEs and its application may enhance the HGT of ARGs in soil, although the bacterial populations of sewage sludge and soil may be quite distinct (Hammesfahr et al, 2008).…”
Section: Introductionmentioning
confidence: 99%